Pengaruh Variasi Suhu Sintering Terhadap Struktur Kristalin Hidroksiapatit Tulang Iga Sapi - Murzid, Jihan Qothrunada; Suharta, Wayan Gede; Spardi, I Wayan; Suardana, Putu; Kasmawan, I Gde Antha; Artawan, I Nengah; Prajitno, Djoko Hadi (Kappa Journal, 2023)
A study entitled " The Effect of Sintering Temperature Variations on the Crystalline Structure of Bovine Bone Hydroxyapatite" has been carried out. The aim of this research is to understand how the sintering temperature influences the hydroxyapatite lattice parameters and to understand how the sintering temperature influences the volume and density of hydroxyapatite. The synthesis process begins with a calcination at 300 °C for one hour, followed by a sintering process with varying temperatures, namely 600 °C, 700 °C and 800 °C for samples A, B and C, respectively. To determine the hydroxyapatite content in the samples, then characterization using XRD was carried out. XRD results analysis was carried out using match3 and Rietica software. Identification results using match3 software obtained the presence of hydroxyapatite compounds and impurity compounds in the form of (Calcium trimagnesium carbonate huntite, Fluorine, Magnesium Hydrogensulfate Hydrate, Sassolite, Zemannite). The volume fraction of hydroxyapatite obtained in this study ranged from 68.6 – 82.8%. The higher the sintering temperature, the greater the volume fraction of hydroxyapatite. The Refinement results show that the higher the sintering temperature, the smaller the value of the lattice parameters in the direction of the a and c axes. Variations in sintering temperature also affect the resulting unit cell volume and density. The higher the sintering temperature, the smaller the unit cell volume, conversely the greater the unit cell density value.